UJI AKTIVITAS ANTI BAKTERI ASAP CAIR YANG BERASAL DARI BATANG KAYU MANIS DAN KULIT KACANG TANAH - -, Yefrida; Aprilina, Farrah; Leone, Indri Ticel; -, Refilda (Jurnal Riset Kimia, 2009)
ABSTRAK Antibacterial agent is a compound that prevent the growth and reproduction of bacteria. Antibacterial activity of liquid smoke is caused by acid and fenolic compound. In this research, we determined antibacterial activity of liquid smoke from stem sweet wood  and nut shell by using diffusion method. Both of liquid smoke have antibacterial activity to Staphylococcus aureus  Eschericia coli population. Their activity almost the same to chloramphenicol, but less than formalin. Keywords : antibacterial activity, liquid smoke, diffusion method